2019
DOI: 10.1097/scs.0000000000005489
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Anthropometry: Normative Data for Caucasian Infants

Abstract: Purpose: Craniofacial anthropometry is a valuable tool for characterization of facial dysmorphology and evaluation of treatment outcomes. Databases of normal anthropometric ranges are limited for infants. The aim of this study is to establish normative data for craniofacial anthropometric measurements in Caucasian infants. Methods: This is a prospective cross-sectional study including Caucasian infants (≤12 months old) that were recruited from a pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…However, human faces are structurally left–right symmetrical content-wise, but not size-wise or function-wise. Therefore, asymmetric faces would be, to some extent, the norm [2,3,4,5,6,7,8,9,10,11]. In a recent and well-delineated 3D facial image study, Kane’s group found that 99.7% of healthy pediatric individuals aged between 0 and 17.8 had less than 3.2 mm of facial asymmetry [9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, human faces are structurally left–right symmetrical content-wise, but not size-wise or function-wise. Therefore, asymmetric faces would be, to some extent, the norm [2,3,4,5,6,7,8,9,10,11]. In a recent and well-delineated 3D facial image study, Kane’s group found that 99.7% of healthy pediatric individuals aged between 0 and 17.8 had less than 3.2 mm of facial asymmetry [9].…”
Section: Discussionmentioning
confidence: 99%
“…From an ecology and evolutionary biology standpoint, perfect bilateral symmetry is defined as the optimal outcome of the development of bilateral traits in the absence of perturbations [1]. For human facial anthropometrics, perfect bilateral symmetry almost never exists, because random variations in asymmetry, within limits, have been recognized as normal and are called facial fluctuating asymmetry [2,3,4,5,6,7,8,9,10,11,12,13,14,15]. When facial asymmetry is clinically obvious (called facial asymmetric deformity, which is more commonly directional rather than fluctuating), surgical or nonsurgical treatment may be required [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations